1962
DOI: 10.1128/jb.84.3.569-576.1962
|View full text |Cite
|
Sign up to set email alerts
|

IN VIVO AND IN VITRO OBSERVATIONS OF LEPTOSPIRA POMONA BY ELECTRON MICROSCOPY

Abstract: Miller, Norman G. (University of Nebraska College of Medicine, Omaha) and Richard B. Wilson . In vivo and in vitro observations of Leptospira pomona by electron microscopy. J. Bacteriol. 84: 569–576. 1962.— Leptospira pomona 3341 was observed by electron microscopy, after the preparation of thin sections from culture material and from infected hamster tissue. The external membrane of low electron density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

1963
1963
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 15 publications
1
12
1
Order By: Relevance
“…Results of this study indicate that leptospires enter the kidney hematogenously, migrate through vascular endothelium, persist in the interstitial spaces, and emigrate via the lateral intercellular junctions to reach the tubular lumina. Absence of intact leptospires within tubular epithelial cells agrees with other ultrastructural studies [9,10,19,20,22,23]. Kinetically, the disease may be divided artificially into an "interstitial phase" characterized by edema, vasculitis and leptospiremia, followed by a "tubular phase" during which leptospires are predominantly associated with microvilli of the proximal convoluted tubular lumina.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Results of this study indicate that leptospires enter the kidney hematogenously, migrate through vascular endothelium, persist in the interstitial spaces, and emigrate via the lateral intercellular junctions to reach the tubular lumina. Absence of intact leptospires within tubular epithelial cells agrees with other ultrastructural studies [9,10,19,20,22,23]. Kinetically, the disease may be divided artificially into an "interstitial phase" characterized by edema, vasculitis and leptospiremia, followed by a "tubular phase" during which leptospires are predominantly associated with microvilli of the proximal convoluted tubular lumina.…”
Section: Discussionsupporting
confidence: 86%
“…Leptospiruria may persist in subclinical, chronic infection and may playa significant role in transmission of the disease to other pigs as well as to cattle [14], man [27], and wild rodents [4,10]. Ultrastructural studies of the kidney in acute leptospirosis largely have been confined to laboratory rodents such as the guinea pig [9], rat (10], mouse (20], and hamster (22,23]. Studies of renal lesions of sheep with experimental leptospirosis show that leptospires in larger mammals are associated with the microvillous border of proximal convoluted tubules [19].…”
mentioning
confidence: 99%
“…Several histopathological studies of leptospirosis have been reported previously, and these mainly focused on the description of lesions observed in the liver and the kidneys [16–18]. In experimental infection of Syrian hamsters, pathogenic leptospires were observed in the liver, in large number in the intercellular spaces, without systematic alterations of the surrounding hepatocytes [19].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated leptospires inside cells in various organs from experimentally infected animals (6,8), and Rose et al (10) showed by fluorescent-antibody techniques that leptospires could attain intracellularity in monkey kidney cells. In this study, we showed that pathogenic leptospires can penetrate tight-junctioned epithelial and endothelial cell monolayers in a chemotaxis chamber-filter membrane assembly, while the nonpathogenic leptospires tested could not invade to significant extent.…”
Section: Figmentioning
confidence: 97%